2015
DOI: 10.3390/polym7010134
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Thermo-Responsive Molecular Layers from Self-Assembling Elastin-Like Oligopeptides Containing Cell-Binding Domain for Tissue Engineering

Abstract: Novel thermo-responsive elastin-like oligopeptides containing cell-binding epitope (Arg-Gly-Asp-Ser sequence); arginine-glycine-aspartic acid-serine (RGDS)-elastin-like peptides (ELP) and RGDS-deg-ELP; were newly prepared as building blocks of self-assembled molecular layer for artificial extra cellular matrix. A detailed analysis of the conformation of the oligo(ELP)s in water and their self-assembling behavior onto hydrophobic surfaces were performed by using circular dichroism, Fourier transform infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Atomic force microscopy (AFM) showed that the MELPs coupled with three phenylalanine residues (FFF‐ELPs) self‐assembled into micelle structures (Figure b; Figure S4, Supporting Information). In a temperature‐ramp circular dichroism (CD) study, FFF‐ELPs underwent a gradual coil‐to‐β‐spiral transition similar to the thermal folding behavior of several ELPs in other studies (Figure c) . Based on these results, we determined that the consecutive NAAs can suggest the thermoresponsiveness to MELPs through a phase transition mechanism mediated by micelle self‐assembly.…”
Section: Resultssupporting
confidence: 65%
“…Atomic force microscopy (AFM) showed that the MELPs coupled with three phenylalanine residues (FFF‐ELPs) self‐assembled into micelle structures (Figure b; Figure S4, Supporting Information). In a temperature‐ramp circular dichroism (CD) study, FFF‐ELPs underwent a gradual coil‐to‐β‐spiral transition similar to the thermal folding behavior of several ELPs in other studies (Figure c) . Based on these results, we determined that the consecutive NAAs can suggest the thermoresponsiveness to MELPs through a phase transition mechanism mediated by micelle self‐assembly.…”
Section: Resultssupporting
confidence: 65%
“…The LCST of P(HPMA-Lacn) could be tuned in the range of 10–65 °C by varying the grafting density of lactate-containing side chains [ 65 ]. Moreover, ELPs are protein-based materials with the ability to capture drug molecules by undergoing LCST-like phase transition when the polymer solution is heated above its transition temperature [ 68 ]. They are widely used in drug delivery systems owing to their excellent biocompatible and biodegradable properties.…”
Section: Temperature-sensitive Assembliesmentioning
confidence: 99%
“…Such a phenomenon is usually termed inverse temperature transition (ITT) [13,19,20], which is suggested to be driven by dehydration of the hydrophobic valine side chains [21]. Very interestingly, short elastin-derived peptides with limited number (usually 1–5) of the repeating β-turn units have been shown to have similar temperature-sensitive conformational changes as ELPs [20,21,22,23,24,25,26,27,28,29]. Reiersen et al showed that a single VPGVG unit can act as a thermodynamically independent unit to undergo the temperature-induced extended‒β-turn transition [21].…”
Section: Introductionmentioning
confidence: 99%